2014
DOI: 10.1158/1055-9965.epi-14-0667
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Sex Hormones and Terminal Duct Lobular Unit Involution of the Normal Breast

Abstract: Background Terminal duct lobular units (TDLUs) are the predominant source of breast cancers. Lesser degrees of age-related TDLU involution have been associated with increased breast cancer risk, but factors that influence involution are largely unknown. We assessed whether circulating hormones, implicated in breast cancer risk, are associated with levels of TDLU involution using data from the Susan G. Komen Tissue Bank (KTB) at the Indiana University Simon Cancer Center (2009-2011). Methods We evaluated thre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 54 publications
3
23
1
Order By: Relevance
“…This work extends prior research in this cohort linking decreased TDLU involution to increased risk of developing breast cancer [7, 15]. We note that several groups have developed automated methods to assess TDLU histology and to estimate levels of involution [15, 17, 18, 33, 34] that agree well with visual assessment. Hence, we view visual assessment of involution levels as a temporary approach to advance this area as automated algorithms are developed.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This work extends prior research in this cohort linking decreased TDLU involution to increased risk of developing breast cancer [7, 15]. We note that several groups have developed automated methods to assess TDLU histology and to estimate levels of involution [15, 17, 18, 33, 34] that agree well with visual assessment. Hence, we view visual assessment of involution levels as a temporary approach to advance this area as automated algorithms are developed.…”
Section: Discussionsupporting
confidence: 80%
“…Prior analyses demonstrating associations between breast cancer risk factors and the TDLU involution metrics evaluated here support that these are biologically plausible markers of risk [11, 16, 17]. Levels of TDLU involution increase with age and menopause, paralleling the slower rise in breast cancer incidence rates around age 50 years, a surrogate for menopause [24].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Up to 10 TDLUs were evaluated for maximum diameter as “TDLU span” (measured with an electronic ruler in microns) to provide reliable estimates (17). A semi-automated image analysis tool was used to estimate the number of acini per TDLU as previously described (18, 19). Median values for each woman were used as summary measures of TDLU span and acini count.…”
Section: Methodsmentioning
confidence: 99%
“…One previous study of TDLU involution among women without BBD measured serum estradiol using an immunoassay and reported that elevated estradiol levels were associated with higher TDLU count [21]. Herein, we used a high-performance liquid chromatography-tandem mass spectrometry (LC/MS-MS) assay to refine measurements and extended the analysis to examine detailed patterns of estrogen metabolism in relation to highly reliable measures of TDLUs and acini count/TDLU in the background normal breast tissue from women undergoing diagnostic breast biopsy.…”
Section: Introductionmentioning
confidence: 99%